2011
DOI: 10.1071/an11010
|View full text |Cite
|
Sign up to set email alerts
|

Pasture systems to improve productivity of sheep in south-western Victoria 2. Animal production from ewes and lambs

Abstract: Two pasture systems (Typical, Upgraded) were compared at five on-farm sites across south-western Victoria between 1990 and 1996. The Typical pasture treatment mimicked the pastures common in the region, with volunteer annual-based species fertilised with ~5 kg/ha.year phosphorus (P). The Upgraded pasture treatment was sown to phalaris, perennial ryegrass and subterranean clover using cultivars recommended for the particular area. Higher rates of fertiliser (13–25 kg/ha.year P) plus other nutrients were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The end point from a reproductive perspective for farmers is often the numbers of lambs weaned per ewe presented for breeding. Kleemann et al (2006) in an across-flock analysis with Merino ewes, Newton et al (1980) with Masham ewes, and Saul et al (2011) with Merino ewes all reported that BCS at breeding and/or mid-pregnancy was positively correlated with the number of lambs weaned per ewe exposed to the ram. Vatankhah et al (2012), with Lori-Bakhtiari ewes, reported that BCS at breeding had a positive effect on the number of lambs weaned per ewe, but only to a BCS of 3.0 before it plateaued.…”
Section: Effect Of Bcs On Ewe Reproductive Traitsmentioning
confidence: 92%
“…The end point from a reproductive perspective for farmers is often the numbers of lambs weaned per ewe presented for breeding. Kleemann et al (2006) in an across-flock analysis with Merino ewes, Newton et al (1980) with Masham ewes, and Saul et al (2011) with Merino ewes all reported that BCS at breeding and/or mid-pregnancy was positively correlated with the number of lambs weaned per ewe exposed to the ram. Vatankhah et al (2012), with Lori-Bakhtiari ewes, reported that BCS at breeding had a positive effect on the number of lambs weaned per ewe, but only to a BCS of 3.0 before it plateaued.…”
Section: Effect Of Bcs On Ewe Reproductive Traitsmentioning
confidence: 92%
“…site or 33 months of age at the WA site, depending on whether the maternal environment was defined as the nutritional treatments, the liveweight profile of individual dams or the birth and rear type of the progeny themselves. Nevertheless, the cumulative difference between the extreme nutritional treatments that covered the range typical of those experienced by many Merino ewes during pregnancy and lactation on commercial farms across southern Australia (Kelly 1992;Kleemann and Walker 2005;Saul et al 2011), was~1.1 kg of clean wool and 0.2 mm over five shearings at the Vic. site and 0.8 kg of clean wool over three shearings at the WA site.…”
Section: Discussionmentioning
confidence: 99%
“…According to Saul et al (2011), a trial in south-western Victoria over 6 years showed that grazing systems with upgraded pastures resulted in a 75% increase in stocking rate, a higher condition score by 0.3, 13% more lambs born and 6% more lambs marked and weaned, all without any increase in the level of supplementary feed required. Therefore, it could be expected that the farmlets might also differ in reproductive efficiency; given the fat scores were below target (score of 3), reproductive performance is likely to have been below the potential for fine wool (16 m) ewes.…”
Section: Discussionmentioning
confidence: 99%